Copper-doped silicon carbide composite material and preparation method and application thereof

The copper-doped silicon carbide composite material prepared by arc plasma cracking technology solves the problem of limited electromagnetic wave absorption performance of existing silicon carbide-based materials, and achieves excellent microwave absorption performance and wide bandwidth absorption effect, which is suitable for the needs of high-performance wave absorption materials.

CN119822372AActive Publication Date: 2025-04-15ZHEJIANG UNIV

Patent Information

Application Number
CN202411252473.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-04-15
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The electromagnetic wave absorption performance of existing silicon carbide-based materials is limited, making it difficult to meet the needs of high-performance wave absorption materials, especially in the stealth needs in the military and defense fields.

Method used

Through arc plasma cracking technology, precursors containing silicon carbon (such as organochlorosilane) are treated, and the copper anode and chlorine plasma are used to prepare copper-doped silicon carbide composite materials. This method not only improves the conductivity and magnetic properties of the material, but also introduces additional interface and lattice defects, enhancing the electromagnetic wave energy loss pathway.

Benefits of technology

The prepared copper-doped silicon carbide composite material has excellent microwave absorption performance and large effective absorption bandwidth, which can effectively reduce or eliminate the reflection and transmission of electromagnetic waves and improve the absorption rate of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822372A_ABST
    Figure CN119822372A_ABST
Patent Text Reader

Abstract

The invention provides a copper-doped silicon carbide composite material and a preparation method and application thereof, and relates to the technical field of electromagnetic wave absorbing materials. The preparation method of the copper-doped silicon carbide composite material provided by the invention comprises the following steps: performing arc plasma cracking on a precursor containing silicon and carbon to obtain the copper-doped silicon carbide composite material, the precursor containing silicon and carbon comprises organic chlorosilane; an anode adopted by the arc plasma cracking comprises copper. The prepared copper-doped silicon carbide composite material has excellent electromagnetic wave absorption performance and large effective absorption bandwidth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to a copper-doped silicon carbide composite material and a preparation method and application thereof. Background Art

[0002] Electromagnetic waves play an important role in modern information life, but with the development of technology leading to the widespread popularization of electronic devices, the electromagnetic waves will also cause a certain degree of electromagnetic pollution, affecting the operation of precision instruments and endangering human health. With the development of national defense construction, higher requirements are also put forward for the stealth of weapons and equipment and military facilities. Therefore, the research of high-performance absorbing materials is of great significance to national defense and people's livelihood. In order to solve these problems, researchers have developed electromagnetic wave absorbing materials that can convert electromagnetic energy into heat or other forms of energy, consume electromagnetic radiation from the source, thereby protecting human health and improving the performance of equipment.

[0003] Electromagnetic wave absorbing materials are materials that can effectively absorb electromagnetic waves into the matrix and achieve efficient attenuation. The essence is to convert the energy of electromagnetic waves into internal energy and dissipate it. According to different wave absorption mechanisms, the common electromagnetic wave absorbing materials currently include magnetic loss materials and dielectric loss materials. Silicon carbide-based materials are common dielectric loss materials, but their intrinsic wave absorption performance is limited. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a copper-doped silicon carbide composite material and a preparation method and application thereof. The copper-doped silicon carbide composite material prepared by the present invention has excellent electromagnetic wave absorption performance and a large effective absorption bandwidth.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a copper-doped silicon carbide composite material, comprising the following steps:

[0007] A silicon-carbon-containing precursor is subjected to arc plasma cracking to obtain a copper-doped silicon carbide composite material; the silicon-carbon-containing precursor includes organic chlorosilane; and the anode used in the arc plasma cracking includes copper.

[0008] Preferably, the arc power of the arc plasma cracking is 1-100 kW.

[0009] Preferably, the arc starting atmosphere gas for arc plasma cracking includes one or more of argon, nitrogen, hydrogen and helium.

[0010] Preferably, the flow rate of the arc starting atmosphere gas for arc plasma cracking is 0.2 to 30 L / min.

[0011] Preferably, the organochlorosilane includes one or more of methylsilicon trichloride, dimethylsilicon dichloride and trimethylchlorosilane.

[0012] Preferably, the feed amount of the silicon-carbon-containing precursor is 0.1-2000 g / min.

[0013] Preferably, after the arc plasma cracking, the obtained solid product is sequentially subjected to alkali washing and drying to obtain the copper-doped silicon carbide composite material.

[0014] The present invention provides a copper-doped silicon carbide composite material prepared by the preparation method described in the above technical solution.

[0015] Preferably, the crystal form of silicon carbide in the copper-doped silicon carbide composite material is β-type.

[0016] The present invention provides application of the copper-doped silicon carbide composite material described in the above technical solution in a wave-absorbing material.

[0017] The present invention provides a method for preparing a copper-doped silicon carbide composite material. The present invention uses copper as an anode, introduces organic chlorosilane as a raw material, and utilizes the high activity of Cl ions while preparing silicon carbide to thermally excite and chemically peel the copper anode, so that copper enters the silicon carbide lattice to obtain a copper-doped silicon carbide composite material. In the present invention, the electrical conductivity and magnetic properties of copper have good electromagnetic wave absorption capacity in the microwave frequency band, and can effectively convert electromagnetic wave energy into heat energy, thereby reducing or eliminating reflection and transmission, and improving the absorption rate of the material. At the same time, copper doping can introduce additional interface and lattice defects, increase the electromagnetic wave energy loss path of the material, and multiple loss mechanisms help to expand the absorption bandwidth of the material. The copper-doped silicon carbide composite material prepared by the present invention has excellent microwave absorption performance and a large effective absorption bandwidth. The preparation method provided by the present invention is simple and suitable for promotion and application.

[0018] The beneficial effects of the present invention are as follows:

[0019] The present invention uses organic chlorosilane as a silicon-carbon precursor, which is low-cost, safe and efficient, and can provide silicon and carbon at the same time to prepare silicon carbide; the chlorine element will form chlorine plasma in the plasma, which has higher activity and stimulates more copper to enter the system;

[0020] The present invention utilizes the dual effects of arc thermal excitation and high reactivity of chlorine plasma to complete copper-doped silicon carbide;

[0021] The present invention obtains the dielectric parameters of the copper-doped silicon carbide composite material by means of a vector network analyzer, and calculates based on the transmission line theory that the copper-doped silicon carbide composite material has excellent wave absorbing performance and a wide-band wave absorbing bandwidth;

[0022] The preparation method of the present invention is continuous and efficient, and is a synthesis method that can be used on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the preparation principle of the copper-doped silicon carbide composite material of the present invention;

[0024] Figure 2 XRD diagram of the copper-doped silicon carbide composite material prepared in Examples 1 to 3 of the present invention;

[0025] Figure 3 TEM image of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention;

[0026] Figure 4 HRTEM image of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention;

[0027] Figure 5 This is a graph of reflection loss values ​​of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention;

[0028] Figure 6 This is a graph of the real part of the dielectric loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention;

[0029] Figure 7 This is a graph of the imaginary part of the dielectric loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention;

[0030] Figure 8 A graph showing the tangent value of the dielectric loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention;

[0031] Fig. 9 is a graph of the real part of the magnetic loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention;

[0032] Fig.10 This is a graph of the imaginary part of the magnetic loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention;

[0033] Fig.11 A graph showing the tangent value of the magnetic loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention;

[0034] Fig.12 It is a schematic diagram of the structure of an arc plasma generator;

[0035] Fig.13 is a graph of reflection loss values ​​of the copper-doped silicon carbide composite material prepared in Example 2;

[0036] Fig.14 This is a graph showing the reflection loss value of the copper-doped silicon carbide composite material prepared in Example 3. DETAILED DESCRIPTION

[0037] The present invention provides a method for preparing a copper-doped silicon carbide composite material, comprising the following steps:

[0038] A silicon-carbon-containing precursor is subjected to arc plasma cracking to obtain a copper-doped silicon carbide composite material; the silicon-carbon-containing precursor includes organic chlorosilane; and the anode used in the arc plasma cracking includes copper.

[0039] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0040] The present invention performs arc plasma cracking on a silicon-carbon-containing precursor to obtain a copper-doped silicon carbide composite material. In the present invention, the silicon-carbon-containing precursor includes an organochlorosilane. In the present invention, the organochlorosilane preferably includes one or more of methyl silicon trichloride, dimethyl silicon dichloride and trimethyl chlorosilane. In the present invention, the feed amount of the silicon-carbon-containing precursor is preferably 0.1 to 2000 g / min, more preferably 0.175 to 2 g / min, and further preferably 0.5 to 1 g / min. In a specific embodiment, the feed amount of the silicon-carbon-containing precursor can be 0.5 g / min, 1 g / min, 2 g / min, 100 g / min, 500 g / min, 1000 g / min or 1500 g / min. While the present invention uses carbon-containing chlorosilane as a precursor containing carbon and silicon to prepare silicon carbide, it uses the Cl element to form a plasma high activity state in a plasma environment, which is beneficial to improve the doping rate and doping effect of copper.

[0041] In the present invention, the anode used in the arc plasma cracking comprises copper, and is preferably a copper sleeve.

[0042] In the present invention, the arc power of the arc plasma cracking is preferably 1 to 100 kW, more preferably 2 to 10 kW, and further preferably 5 to 8 kW. In a specific embodiment, the arc power of the arc plasma cracking can be 1.6 kW, 2.2 kW, 2.9 kW, 10 kW, 20 kW, 30 kW, 40 kW, 50 kW, 60 kW, 70 kW, 80 kW or 90 kW.

[0043] In the present invention, the arc-starting atmosphere gas for the cracking of the arc plasma preferably includes one or more of argon, nitrogen, hydrogen and helium, and is more preferably argon. In the present invention, the flow rate of the arc-starting atmosphere gas for the cracking of the arc plasma is preferably 0.2 to 30 L / min, more preferably 1 to 20 L / min, and further preferably 2 to 10 L / min. In a specific embodiment, the flow rate of the arc-starting atmosphere gas for the cracking of the arc plasma can be 1 L / min, 2 L / min, 5 L / min, 10 L / min, 15 L / min, 20 L / min or 25 L / min. The present invention uses the above-mentioned arc-starting atmosphere gas to create a reaction atmosphere and control the reaction pressure to generate an arc.

[0044] In the present invention, after the arc plasma cracking, it is preferred that the solid product obtained is sequentially alkali washed and dried to obtain a copper-doped silicon carbide composite material. In a specific embodiment of the present invention, the arc plasma cracking forms gaseous copper-doped silicon carbide; the gaseous copper-doped silicon carbide is cooled in the arc plasma generator to form a solid product. In the present invention, the alkali solution used in the alkali washing is preferably a NaOH solution; the concentration of the NaOH solution is preferably 0.01-1 mol / L, more preferably 0.1-0.5 mol / L. In the present invention, the amount ratio of the solid product to the NaOH solution is preferably 2g:100mL. In the present invention, the alkali washing is preferably carried out under ultrasonic conditions; the ultrasonic time is preferably 30min. The present invention removes HCl and residual raw materials adsorbed on the surface of the solid product by alkali washing. The present invention preferably performs rinse filtration after the alkali washing. In the present invention, the washing liquid used in the rinse filtration is preferably water, more preferably deionized water. In a specific embodiment of the present invention, the rinse filtration refers to washing while filtration. In the present invention, the drying temperature is preferably 105°C; the drying time is preferably 2 hours. In the present invention, the drying is preferably carried out in a vacuum oven.

[0045] In a specific embodiment of the present invention, the arc plasma cracking is carried out in an arc plasma generator; the structure of the arc plasma generator is as follows: Fig.12 As shown, the anode of the arc plasma generator is a copper sleeve, and the cathode is a rod-shaped structure; the material of the cathode is graphite. In the present invention, the preparation method of the copper-doped silicon carbide composite material is preferably: using organic chlorosilane as a silicon-carbon precursor, arcing under the action of arc-starting atmosphere gas, copper sleeve as an anode, in a plasma environment, using arc plasma method to crack the silicon-carbon precursor to obtain a solid product; removing HCl and residual raw materials adsorbed on the surface of the solid product by alkaline washing with NaOH solution, rinsing, filtering and drying to obtain the copper-doped silicon carbide composite material.

[0046] As an embodiment of the present invention, the preparation method of the copper-doped silicon carbide composite material is as follows: argon is used to replace the air in the arc plasma generator, and the power supply is started in the argon atmosphere to ignite the arc. After the operation is stable, the methyl silicon trichloride in the bubbler is carried into the arc plasma generator by the argon gas for cracking to form gaseous copper-doped silicon carbide, and the gaseous copper-doped silicon carbide is deposited inside the arc plasma generator along the direction of the plasma jet, and a solid product is collected to obtain a solid product, and then the HCl and residual raw materials adsorbed on the surface of the solid product are removed by alkaline washing with a NaOH solution, and the copper-doped silicon carbide composite material is obtained after rinsing, filtration and drying.

[0047] The present invention provides a copper-doped silicon carbide composite material prepared by the preparation method described in the above technical scheme. In the present invention, the crystal form of silicon carbide in the copper-doped silicon carbide composite material is preferably β-type. In a specific embodiment of the present invention, the silicon carbide in the copper-doped silicon carbide composite material is β-SiC. In the present invention, the copper-doped silicon carbide composite material is preferably a copper-doped nano-silicon carbide composite material; the size of the copper-doped silicon carbide composite material is preferably 20 to 500 nm, more preferably 50 to 100 nm. In the present invention, copper is doped into the SiC lattice in the form of a copper-silicon solid solution to replace the C atoms therein. In the present invention, the copper-silicon solid solution preferably includes Cu 6.69 In a specific embodiment of the present invention, the copper chloride compounds such as CuCl2 formed by oxidation of Cl and remaining on the surface are removed during the rinse and filtration process.

[0048] The present invention provides the use of the copper-doped silicon carbide composite material described in the above technical solution in a wave absorbing material, preferably used as an electromagnetic wave absorbing material, and more preferably used as a microwave absorbing material.

[0049] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The structure of the arc plasma generator used in the embodiment is as follows Fig.12 As shown, the anode of the arc plasma generator is a copper sleeve, and the cathode is a rod-shaped structure; the cathode is made of graphite.

[0051] Figure 1 This is a schematic diagram of the present invention for preparing a copper-doped silicon carbide composite material in a copper sleeve using organic chlorosilane.

[0052] Example 1

[0053] Argon is used to replace the air in the arc plasma generator, and argon is continuously introduced at a flow rate of 2 L / min. The power supply is started in the argon atmosphere to ignite the arc, and the arc power is set to 2.2 kW. After the operation is stable, methyl silicon trichloride in the bubbler is brought into the arc plasma generator by argon for cracking, and the feed rate is 175 mg / min to form gaseous copper-doped silicon carbide. The gaseous copper-doped silicon carbide is deposited inside the arc plasma generator along the direction of the plasma jet, and a solid product is collected;

[0054] 2 g of the collected solid product was added to 100 mL of a 0.5 mol / L NaOH solution and ultrasonicated for 30 min. The solid material was filtered and washed with deionized water. The solid material was placed in a vacuum oven at 105° C. for 2 h to obtain a copper-doped silicon carbide composite material.

[0055] Example 2

[0056] The preparation method is basically the same as that of Example 1, except that the arc power is adjusted to 1.6 kW.

[0057] Example 3

[0058] The preparation method is basically the same as that of Example 1, except that the arc power is adjusted to 2.9 kW.

[0059] Test Case

[0060] Examples 1 to 3 illustrate the influence of different arc powers on the copper doping effect.

[0061] Figure 2 The XRD spectra of the copper-doped silicon carbide composite material prepared under different arc power conditions of the present invention are shown in FIG. Figure 2 It can be seen that there are obvious characteristic peaks at 26.1°, 28.8°, 35.7°, 41.4°, 60.2° and 71.8°. The 26.1° position is the diffraction plane of the graphite (002) crystal plane, and the 28.8° position is the diffraction plane of the CuCl2 (111) crystal plane; the 35.7°, 41.4°, 60.2° and 71.8° positions correspond to the (111), (200), (220) and (311) crystal planes of β-SiC, respectively. Zooming in on the range of 43° to 50°, it is observed that the peaks at 43.2° and 46.3° correspond to Cu 6.69The peaks at 44.6° and 45.2° correspond to the (012) and (300) crystal planes of Cu3Si. This indicates that a variety of Cu-Si solid solutions appear in the composite material, and Cu can quickly enter the β-SiC lattice at high temperature to achieve copper doping due to its high diffusion coefficient.

[0062] Figure 3 This is a TEM image of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention. It is found that there are obvious contrast differences in the particles, and the diameter of the darker particles is less than 10 nm.

[0063] Figure 4 This is the HRTEM image of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention. By comparing the parameters of the standard card, it can be determined that a copper-silicon solid solution is formed, which proves the feasibility of preparing the copper-doped silicon carbide composite material by the method of the present invention.

[0064] Figure 5 This is a reflection loss value diagram of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention. It can be seen from the figure that when the copper-doped silicon carbide composite material has a matching thickness of 8 mm, RL min The value at 14.52GHz is -44.56dB, and the maximum absorption bandwidth is up to 5.2GHz, reaching the strength index of excellent absorbing materials (RL min <-30dB), indicating that the copper-doped silicon carbide composite material exhibits excellent microwave absorbing performance.

[0065] Figure 6 The real part value diagram of the dielectric loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention shows an overall decrease in the test band (2 to 18 GHz).

[0066] Figure 7 The imaginary part value graph of the dielectric loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention shows a trend of first decreasing in the 2-8 GHz frequency band and then increasing in the 8-18 GHz range, indicating that the copper-doped silicon carbide composite material has directionality in the loss of high-frequency electric fields.

[0067] Figure 8 This is a graph of the tangent value of the dielectric loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention, and its value increases significantly in the range of 15 to 17 GHz.

[0068] Fig. 9 This is a graph of the real part of the magnetic loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention. Its value fluctuates slightly in the frequency band of 2 to 18 GHz, and its value changes slowly between 0.9 and 1.1.

[0069] Fig.10This is a graph of the imaginary part of the magnetic loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention, and its value oscillates significantly in the frequency range of 2 to 18 GHz.

[0070] Fig.11 This is a graph of the tangent value of the magnetic loss of the copper-doped silicon carbide composite material prepared in Example 1 of the present invention, and its value oscillates significantly in the frequency range of 2 to 18 GHz.

[0071] Combination Figures 1 to 11 As shown in the figure, when the copper-doped silicon carbide composite material is matched with a thickness of 8 mm, RL min The value at 14.52GHz is -44.56dB, and the maximum absorption bandwidth is up to 5.2GHz, reaching the strength index of excellent absorbing materials (RL min <-30dB), indicating that the copper-doped silicon carbide composite material exhibits excellent wave absorption performance. At the same time, the tangent value of the magnetic loss is greater than the tangent value of the dielectric loss, indicating that the magnetic loss of the copper-doped silicon carbide composite material dominates its overall energy loss, which indirectly proves that copper doping into nano-silicon carbide composite materials exhibits a magnetic loss mechanism similar to that of magnetic materials such as iron, cobalt and nickel.

[0072] Fig.13 This is a graph of reflection loss values ​​of the copper-doped silicon carbide composite material prepared in Example 2. Fig.14 This is a graph showing the reflection loss value of the copper-doped silicon carbide composite material prepared in Example 3. Figures 13-14 It can be seen that the copper-doped silicon carbide composite material prepared by the present invention has excellent microwave absorption performance.

[0073] According to the preparation process of the copper-doped silicon carbide composite material and the test results of the microwave absorption performance, the copper-doped silicon carbide composite material prepared under the condition of an arc power of 2.2 kW in Example 1 has the best microwave absorption performance.

[0074] Influence of different arc starting atmosphere gases on copper doping effect in Examples 4 to 6

[0075] Argon is used to replace the air in the arc plasma generator, and an arc starting atmosphere gas with a flow rate of 2 L / min is continuously introduced. In the atmosphere of the arc starting atmosphere gas (argon, nitrogen, and helium correspond to Examples 4, 5, and 6, respectively), a power supply is started to ignite the arc, and the arc power is set to 5 kW. After the operation is stable, the methyl silicon trichloride in the bubbler is brought into the interior of the arc plasma generator by the arc starting atmosphere gas for cracking. The feed amount is 0.5 g / min to form gaseous copper-doped silicon carbide. The gaseous copper-doped silicon carbide is deposited inside the arc plasma generator along the direction of the plasma jet, and a solid product is collected;

[0076] 2 g of the collected solid product was added to 100 mL of a 0.5 mol / L NaOH solution and ultrasonicated for 30 min. The solid material was filtered and washed with deionized water. The solid material was placed in a vacuum oven at 105° C. for 2 h to obtain a copper-doped silicon carbide composite material.

[0077] According to the test results of Examples 4 to 6, the copper doping effects of different arc starting atmosphere gases are similar.

[0078] Examples 7-9 Effects of different organochlorosilanes on copper doping

[0079] Argon was used to replace the air in the arc plasma generator, and argon was continuously introduced at a flow rate of 2 L / min. The power supply was started in the argon atmosphere to ignite the arc, and the arc power was set to 5 kW. After the operation was stable, the organochlorosilane (Example 7, Example 8, and Example 9 corresponded to methyl silicon trichloride, dimethyl silicon dichloride, and trimethyl chlorosilane, respectively) in the bubbler was brought into the arc plasma generator by argon to be cracked, and the feed amount was 0.5 g / min to form gaseous copper-doped silicon carbide. The gaseous copper-doped silicon carbide was deposited inside the arc plasma generator along the direction of the plasma jet, and a solid product was collected;

[0080] 2 g of the collected solid product was added to 100 mL of a 0.5 mol / L NaOH solution and ultrasonicated for 30 min. The solid material was filtered and washed with deionized water. The solid material was placed in a vacuum oven at 105° C. for 2 h to obtain a copper-doped silicon carbide composite material.

[0081] According to the test results of Examples 7 to 9, the carbon-containing organochlorosilanes can all be successfully used to prepare copper-doped silicon carbide composite materials, wherein the stoichiometric ratio of carbon to silicon in methyl silicon trichloride is 1:1, and can provide silicon atoms and carbon atoms according to the chemical formula of silicon carbide (SiC), making them the preferred organochlorosilane raw materials.

[0082] Influence of different feed amounts on copper doping effect in Examples 10-12

[0083] Argon was used to replace the air in the arc plasma generator, and argon was continuously introduced at a flow rate of 2 L / min. The power supply was started in the argon atmosphere to ignite the arc, and the arc power was set to 10 kW. After the operation was stable, the methyl silicon trichloride in the bubbler was brought into the arc plasma generator by argon for cracking. The corresponding feed amounts of Example 10, Example 11, and Example 12 were 0.5 g / min, 1 g / min, and 5 g / min, respectively, to form gaseous copper-doped silicon carbide. The gaseous copper-doped silicon carbide was deposited inside the arc plasma generator along the direction of the plasma jet, and a solid product was collected;

[0084] 2 g of the collected solid product was added to 100 mL of a 0.5 mol / L NaOH solution and ultrasonicated for 30 min. The solution was rinsed and filtered with deionized water. The obtained solid material was placed in a vacuum oven at 105° C. for 2 h to obtain a copper-doped silicon carbide composite material.

[0085] According to the test results of Examples 10 to 12, for an arc power of 10 kW, the preferred feed rate is 1 g / min while ensuring the copper doping effect and improving energy utilization.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a copper-doped silicon carbide composite material, comprising the following steps: The precursor containing silicon and carbon is subjected to arc plasma pyrolysis to obtain a copper-doped silicon carbide composite material; the precursor containing silicon and carbon includes organic chlorosilane; The arc plasma dissociation employs an anode comprising copper.

2. The preparation method according to claim 1, characterized in that: The arc power of the arc plasma cracking is 1-100 kW.

3. The preparation method according to claim 1, characterized in that: The arc starting atmosphere gas for arc plasma cracking includes one or more of argon, nitrogen, hydrogen and helium.

4. The preparation method according to claim 3, characterized in that: The flow rate of the arc starting atmosphere gas for arc plasma cracking is 0.2 to 30 L / min.

5. The preparation method according to claim 1, characterized in that: The organochlorosilane includes one or more of methylsilicon trichloride, dimethylsilicon dichloride and trimethylchlorosilane.

6. The preparation method according to claim 1 or 5, characterized in that: The feed rate of the silicon-carbon-containing precursor is 0.1-2000 g / min.

7. The preparation method according to claim 1, characterized in that: After the arc plasma cracking, the obtained solid product is sequentially subjected to alkali washing and drying to obtain the copper-doped silicon carbide composite material.

8. The copper-doped silicon carbide composite material prepared by the preparation method according to any one of claims 1 to 7.

9. The copper-doped silicon carbide composite material according to claim 8, characterized in that: The crystal form of silicon carbide in the copper-doped silicon carbide composite material is β-type.

10. Use of the copper-doped silicon carbide composite material according to any one of claims 8 to 9 in wave absorbing materials.

Citation Information

Patent Citations

  • An organic electroluminescence device with super-thin layer structure

    CN101217187A

  • Manufacturing method for semiconductor device

    CN102915952A

  • Wear-proof and scratch-proof cover glass for touch screen and preparation method of cover glass

    CN107540238A

  • Nanowire network

    CN117642242A

  • Single crystal sic growth method

    JP3043744B1

Cited By

  • Copper-doped silicon carbide composite material, and preparation method therefor and use thereof

    WO2026052165A1